We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

#1**+3 **

(a+1)x^2 - (a^2 + 1)x + 2a^3 - 6 = 0

By inspection...let a = 0 and we have

x^2 - x - 6 = 0 factoring, we get

(x - 3) ( x + 2) = 0

And the two roots are x = 3 and x = -2

CPhill Oct 25, 2018

#2**+1 **

P.S.....there may be other solutions for "a"....I don't know.....perhaps someone else knows another way to obtain all of them, if there are more...!!!!

CPhill
Oct 25, 2018